2016
DOI: 10.1016/j.ijheh.2016.04.008
|View full text |Cite
|
Sign up to set email alerts
|

On-plot drinking water supplies and health: A systematic review

Abstract: Many studies have found that household access to water supplies near or within the household plot can reduce the probability of diarrhea, trachoma, and other water-related diseases, and it is generally accepted that on-plot water supplies produce health benefits for households. However, the body of research literature has not been analyzed to weigh the evidence supporting this. A systematic review was conducted to investigate the impacts of on-plot water supplies on diarrhea, trachoma, child growth, and water-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 85 publications
(144 reference statements)
1
37
0
Order By: Relevance
“…Nearly all of these articles concern Sub‐Saharan Africa. Despite the paucity of published studies and their relatively narrow geographic focus, there is growing recognition of the importance of multiple household water sources and a growing body of literature acknowledges the practice around the world and/or calls for further research (Ahmed & Hossain, ; Brown et al, ; Dos Santos et al, ; Evans et al, ; Foster & Hope, ; Henry, ; Jeuland et al, ; MacDonald et al, ; Overbo et al, ; Shaheed et al, ; Thompson et al, ; Wang et al, ). This dispersed literature lacks consistent vocabulary and methodologies; published studies can be difficult to find; and most articles cite few or no prior studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nearly all of these articles concern Sub‐Saharan Africa. Despite the paucity of published studies and their relatively narrow geographic focus, there is growing recognition of the importance of multiple household water sources and a growing body of literature acknowledges the practice around the world and/or calls for further research (Ahmed & Hossain, ; Brown et al, ; Dos Santos et al, ; Evans et al, ; Foster & Hope, ; Henry, ; Jeuland et al, ; MacDonald et al, ; Overbo et al, ; Shaheed et al, ; Thompson et al, ; Wang et al, ). This dispersed literature lacks consistent vocabulary and methodologies; published studies can be difficult to find; and most articles cite few or no prior studies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, to derive the health benefits associated with improved water quality, high‐quality water must be consumed exclusively throughout the year; even occasionally drinking contaminated water undermines nearly all health gains (Brown & Clasen, ; Enger et al, ; Hunter, ). A consistent water supply has also been associated with increased handwashing and other hygiene practices (Devoto et al, ; Evans et al, ) and decreased diarrhea (Dos Santos et al, ; Overbo et al, ). These studies highlight how temporal changes in water quality and availability challenge development goals and affect health.…”
Section: Introductionmentioning
confidence: 99%
“…We utilized community level provider water source data (similar to Giné-Garriga et al, 2013 and Ntozini et al, 2015) to compute improved water access indicators using a design capacity–based and a distance–based method for six buffer distances ranging from 100 to 1000 m. Although basic access according to the MDGs is constituted by a water source located with 1000 m of the home (UNDG, 2003), research suggests that optimum water use for good hygiene behavior and better health is achieved when an on–plot water source is available with water use dropping substantially when distance to water source exceeds 100 m (Cairncross, 1987; Curtis et al, 1995; Howard & Bartram 2003; Larson et al 2006; Overbo et al, 2016; Pickering & Davis, 2012; Thompson et al, 2001). In our study area, water access within 100 m was rather low (18 – 22%) and contributed mostly by towns with PWSs with a higher average density of public SPs than that of BHs.…”
Section: Discussionmentioning
confidence: 99%
“…Distance, water quality, and price of water are known to influence water use patterns and health benefits offered by improved water sources (Cairncross, 1987; DeGabriele, 2002; Fuest, 2005; Howard & Bartram 2003; Rogers et al, 2002; Overbo et al, 2016; Pickering & Davis, 2012). Households that self–report using an improved water source for the JMP indicator may still extensively rely on unimproved water sources, especially when the improved source is frequently in disrepair, is of poor perceived water quality for domestic purposes, or is too expensive to use exclusively (Kosinski et al, 2016; Kulinkina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This has led to underrepresentation of multiple water source use in household (HH) water management and its relevance for important and timely issues in global WaSH including hygiene, household water quantity needs, and adaptation of water practices by season and climate resilience. A recent review of on-plot drinking water supplies and health found only five adopted [2]. It is considered too time consuming and difficult to implement because of its intricate grid-pattern framework, numerous skip sequences and extensive length.…”
Section: Introductionmentioning
confidence: 99%